Development of an integrated energy system with CO2 capture and utilization in an industrial setting for clean hydrogen and methanol - Akgun, Ibrahim; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study introduces an innovative and environmentally friendly multigeneration system designed to significantly reduce CO2 emissions in steel production while producing clean hydrogen and methanol as two critical fuels for a sustainable energy future. By utilizing advanced carbon capture technology with monoethanolamine (MEA) absorption, the system effectively removes CO2 from steel manufacturing processes and transforms it into valuable methanol. Hydrogen production, powered by wind energy through alkaline electrolysis, plays a central role in this system, showcasing the potential of renewable energy in industrial applications. Beyond its environmental benefits, the current system delivers multiple outputs, including a substantial power output of 5735 kW, a heating effect of 772.6 kW, and a hot water supply of 55 kg/h. To further improve the system performance in specific and sustainability at large, solar energy is integrated into the design, highlighting a commitment to maximizing renewable resource utilization. Furthermore, the system achieves a hydrogen generation rate of 5.75 kg/h and a methanol production rate of 97.95 kg/h. With energy and exergy efficiencies of 60.24 % and 56.58 %, respectively, this system brings a unique approach to industrial decarbonization. Its design not only demonstrates the feasibility of integrating renewable resources into energy-intensive industries but also offers a practical pathway toward cleaner, more sustainable production practices for a greener future.
Keywords: Solar energy; Steel production; Hydrogen; Methanol; Carbon capture; Energy; Exergy; Efficiency; RENEWABLE HYDROGEN; CARBON-DIOXIDE; CONVERSION; CYCLE; Thermodynamics; Energy & Fuels